Odpowiedź :
a)
[tex]4 \frac{1}{3} + x = 11[/tex]
[tex]x = 11 - 4 \frac{1}{3} =10 \frac{3}{3} - 4 \frac{1}{3} = 6 \frac{2}{3} [/tex]
b)
[tex]3x = 14[/tex]
[tex]x = \frac{14}{3} = 4 \frac{2}{3} [/tex]
c)
[tex] \frac{1}{7} x = - 4[/tex]
[tex]x = - 4 \times 7 = - 28[/tex]
d)
[tex]2 - x = - 3[/tex]
[tex] - x = - 3 - 2[/tex]
[tex] - x = - 5[/tex]
[tex]x = \frac{ - 5}{ - 1} = 5[/tex]
Odpowiedź:
Szczegółowe wyjaśnienie:
a/
4 1/3 + x = 11
x = 11 - 4 1/3
x = 10 3/3 - 4 1/3
x = 6 2/3b/
3x = 14 / :3
x = 14/3
x = 4 2/3
c/
1/7 x = - 4 /×7
x = - 28
d/
2 - x = - 3
- x = - 3 - 2
- x = -5 /*(-1)
x = 5